Hutchinson-Gilford Progeria Is a Skeletal Dysplasia - Gordon, Catherine M. (J Bone Miner Res, 2011)
Hutchinson-Gilford Progeria Syndrome (HGPS) is a rare segmental premature aging disorder that affects bone and body composition, among other tissues. We sought to determine if bone density and structural geometry are altered in children with HGPS, and whether relationships exist among these parameters and measures of skeletal anthropometry, body composition, and nutrition. We prospectively enrolled 26 children with HGPS (ages 3.1 to 16.2 years). Outcomes included: anthropometric data; bone age; areal bone mineral density (aBMD) and body composition by dual energy x-ray absorptiometry (DXA); volumetric bone mineral density (vBMD), strength strain index (SSI), and bone structural rigidity calculated from radial transaxial peripheral quantitative computed tomographic (pQCT) images; serum bone biomarkers and hormonal measures; and nutrition assessments. Children with HGPS had low axial aBMD Z-scores by DXA, which improved after adjustment for height age, while differences in radial vBMD by pQCT were less striking. However, pQCT revealed distinct abnormalities in both novel measures of bone structural geometry and skeletal strength at the radius compared to healthy controls. Dietary intake was adequate, confirming that HGPS does not represent a model of malnutrition-induced bone loss. Taken together, these findings suggest that the phenotype of HGPS represents a unique skeletal dysplasia.